2017
DOI: 10.1016/j.asmart.2016.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of magnetic resonance imaging in diagnosing lateral ankle ligament injuries: A comparative study with surgical findings and timings of scans

Abstract: ObjectiveThis study aimed to evaluate the accuracy of magnetic resonance imaging (MRI) in diagnosing lateral ankle ligament injuries and the effect of differences in time duration from injury to MRI.MethodsData were collected prospectively from 82 patients who underwent MRI and lateral ligament reconstruction, and were divided into either acute (≤3 months) or chronic (>3 months) group based on injury interval. Findings were classified as normal, partial, or complete tears of the anterior talofibular ligament (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 31 publications
2
33
0
Order By: Relevance
“…Overall, 15 studies [ 35 49 ] were eligible for this systemic review and are summarized in Table 2 . A total of 695 participants were included.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall, 15 studies [ 35 49 ] were eligible for this systemic review and are summarized in Table 2 . A total of 695 participants were included.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 695 participants were included. In 3 studies [ 39 , 45 , 49 ], participants were divided into acute injury group and chronic injury one, chronic injury groups of which were included in data synthesis. Two studies [ 42 , 44 ] reported inter-rater reliability.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most syndesmosis injuries arise from external rotation of the ankle; among the four ligaments, it is most important to evaluate the AiTFL 6,7 . There have been many attempts to accurately evaluate the pathology of AiTFL and ATFL using MRI 4,8‐12 . There is still a question about the usefulness of the routine ankle MRI protocol for diagnosis of AiTFL and ATFL injury because of the variable diagnostic accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…There is still a question about the usefulness of the routine ankle MRI protocol for diagnosis of AiTFL and ATFL injury because of the variable diagnostic accuracy. MRI sensitivity is about 40–95% and its specificity is 70–97%, which is a wide range 4,9‐11,13‐16 . The reason for this variable diagnostic accuracy may be associated with anatomical features of lateral ankle ligaments.…”
Section: Introductionmentioning
confidence: 99%